Introduction pages, Nova Geodesia 4(1), 2024 - Paul SESTRAS (Nova Geodesia, 2024)
Nova Geodesia (https://novageodesia.ro), Issue 1, Volume 4, 2024: The papers published in this issue represent interesting novelties in different topics of geodetic science or related fields. Nova Geodesia publishes significant papers in geodesy and close topics related to cartography, engineering projects and construction, planetology, hydrography, geography, sociodemographic factors, urban administration, planning and environment, landscape, biodiversity, and ecology. Among the exciting articles, we invite readers to find news about: Monitoring the evolution of a wetland pattern near Addis Ababa with the use of Landsat data (1986-2019); Effect of soil and water conservation practices and slope gradient on organic carbon stocks micronutrients: A case study on Kulkullessa sub-watershed, Eastern Ethiopia; The cross-disciplinary influence of aerial measurement techniques: Exploring archaeological studies through photogrammetry and LiDAR.